Psychological Assistance for Children Victimized by Sexual Violence: Strengthening Their Psychological Resilience - Valensia Callula Almatina; Siti Jaroah (International Conference on Psychology and Education (ICPE), 2025)
This study aims to describe the psychological assistance process provided by the UPTD PPA of Surabaya City to child victims of sexual violence. The research used a descriptive qualitative method, with data collected through in-depth interviews, direct observations, and documentation. The findings indicate that psychological assistance at UPTD PPA Surabaya involves not only counseling but also support during medical procedures, legal processes, and temporary shelter placement. However, several challenges arise in the implementation, including the child's difficulty in disclosing the incident, limited communication abilities among young children, lack of early sexual education, and insufficient support from the social environment and families. Therefore, active involvement of families and communities is crucial to the psychological recovery of child victims of sexual violence.